2013
DOI: 10.1061/(asce)wr.1943-5452.0000361
|View full text |Cite
|
Sign up to set email alerts
|

Classic Optimization Techniques Applied to Stormwater and Nonpoint Source Pollution Management at the Watershed Scale

Abstract: Linear and dynamic programming formulations are introduced for optimizing the placement of distributed best management practices (BMPs) at the watershed scale. The results of linear programming optimization of infiltration-based stormwater management BMPs are compared with the results of genetic algorithm (GA)optimization using a nonlinear distributed model. Additionally, linear and dynamic programming optimization of sediment-trapping BMPs are compared with GA optimization using a nonlinear distributed model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Many causes of impairments for which TMDLs have been developed in the US are typically sediment related. The methods for reducing sediment loading in agricultural landscapes have been studied extensively (Secchi et al 2007;Nigel and Rughooputh 2010;Zhang et al 2010;Limbrunner et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Many causes of impairments for which TMDLs have been developed in the US are typically sediment related. The methods for reducing sediment loading in agricultural landscapes have been studied extensively (Secchi et al 2007;Nigel and Rughooputh 2010;Zhang et al 2010;Limbrunner et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Limbrunner et al . () applied classic optimization techniques applied to stormwater and nonpoint source pollution management at the watershed scale. McGarity () employed system analysis to meet total maximum daily loads (TMDLs) in urban watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2012) developed a watershed-scale design optimization model for stormwater best management practices. Limbrunner et al (2013) applied classic optimization techniques applied to stormwater and nonpoint source pollution management at the watershed scale. McGarity (2013) employed system analysis to meet total maximum daily loads (TMDLs) in urban watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that an integrated simulation‐optimization model that mimics physical processes can be more effective in obtaining optimal decisions for watershed‐scale load reduction [ Ines et al ., ; Luo and You , ; Zou et al ., ; Kaini et al ., ]. For those types of simulation‐optimization framework applications, a watershed‐simulation model provides the baseline numerical representation of spatially variable NPS loads, from which a BMP optimization model can identify optimal BMP types and placements [ Ayvaz and Karahan , ; Limbrunner et al ., ].…”
Section: Introductionmentioning
confidence: 99%